Adaptive control of feed-forward linearization for laser nonlinearity compensation system - Neo, Yun Sheng (2012)
Radio over Fiber technology (RoF) is a promising solution to the next generation wireless access network because of its ability to transmit high capacity data and to be cost effective. However, RoF systems are analog systems which are sensitive to noise and distortions. The RoF links need to have good linearity in order to avoid nonlinear distortions. The primary limitation on the performance of the optical transceiver in RoF links is the nonlinearity of the laser source in the transmitter. The laser source nonlinearities generate intermodulation distortion products which can severely degrade the performance of the RoF links. Hence, various linearization schemes are proposed to compensate the nonlinearity of the laser source, such as feedback, predistortion, and feed-forward. Among the linearization technique, feed-forward linearization is considered as the most effective due to its ability to provide broadband distortion reduction at high frequencies, and reduction in all order of distortions regardless of the laser nonlinear characteristics. However, feed-forward linearization is a relatively sensitive scheme, where its performance is highly influenced by changing operating conditions. Hence, the feedforward linearization system needs to be incorporated with adaptive properties in order to achieve optimization in linearization for more practical implementations. In this thesis, a laser transmitter feed-forward linearization system has been modeled in the commercial software OptiSystem 9.0. The laser transmitter feed-forward linearization system is integrated with the proposed adaptive control system developed in MATLAB through Visual Basic scripting. The results of the cosimulations have achieved significant reductions of over 20 dBm in the third-order intermodulation distortion products for operating frequencies from 5.1 to 5.8 GHz.